FAKTOR-FAKTOR PENENTU KUALITAS HUBUNGAN DALAM PEMBERIAN LAYANAN KREDIT PERBANKAN KEPADA USAHA KECIL SERTA DAMPAKNYA TERHADAP KEPUASAN DAN KOMITMEN NASABAH - Tito Nur Afandi (Journal of Business & Banking, 2014)
Almost half of Indonesian Gross National Product (GNP) is provided by small enterprises. In this case, small enterprises can create competition with the banks to offer their credit services. Some research found that good relationship can increase added value to banks customer of small enterprises owner. In turn, it also increases satisfaction and commitment. This study describes the factors determining relationship quality on banking credit services and small enterprises and its impact to customers satisfaction and commitment. Questionnaires were distributed to 135 small enterprises in Surabaya. The data were analyzed using statistic descriptivemethods to see the factors determining relationship quality, and SEM was employed to analyze the relationship between variables being researched. It shows both kinds of interactions such as service interpersonnel and service environment have a direct positive impact on relationship quality, service environmen consisting of ambience, credit policy and warranty are factors that determined the most relationship quality. The study incorporates the important notion of warranty to the construct of interaction quality between customers and the service environment. Thus, it also supports the hypothesis that factors determining relationship quality show its positivesignificant impact on satisfaction and commitment.